Beyond visual fixations and gaze behaviour. Using pupillometry to examine the mechanisms in the planning and motor performance of a golf putt - Carnegie, E.; Marchant, D.; Towers, S.; Ellison, P. (Human Movement Science, 2020)
The present study assessed the potential value of using pupillometry to explore skill level differences in the allocation of attention during planning and performance of a golf putt across three putting conditions of varying complexity. Although numerous studies have reported on skill level differences in performers' visual search behaviours, performance accuracy and quiet eye duration (QE) across a range of performance settings, few have provided an objective measure of the allocation of attention during task performance. Fourteen participants were assigned to two groups [low handicap (LHG) and high handicap (HHG)] completing ten putts in three conditions; right to left (RL), left to right (LR) and straight (ST) from 1.75 m while wearing a mobile eye tracker. Skill based differences in the allocation of attention during green exploration and skill execution were observed. Pupil constriction observed for both groups during the QE period provides evidence of increased workload directly related to the increased motor task precision required in the physical performance of the putt. LHG had significantly more fixations of longer duration than their HHG counterparts. Distinct differences were also evident between skill levels in relation to number of fixations, fixation duration and QE duration on each putting condition. The significantly longer QE duration and larger pupil constrictions exhibited by skilled performers offer evidence of a distinctive concentration of cognitive activity characterised by highly automated processes.